Vision-based finite-time uncooperative target tracking for UAV subject to actuator saturation. (August 2021) - Sun, Peng; Zhu, Bing; Zuo, Zongyu; Basin, Michael V.
Abstract: In this paper, a vision-based finite-time control is proposed for an unmanned aerial vehicle (UAV) subject to actuator saturation to track an uncooperative target. The finite-time control is designed within a backstepping-type framework, where states of the uncooperative target cannot be measured directly and are estimated by a monocular camera equipped on the UAV. It is proven that, with the given control, the UAV with actuator saturation is capable of reaching the target for a finite settling time. Based on available initial states, the finite settling time can be estimated a priori . The theoretical results are illustrated by a simulation example.